Intergenerational Conflict in The Shadow’s Edge: A Sociological Analysis - Aira Fitya Putti; Rosefina Safitri Lubis; Girlie Kayla Andini; Dinie Larasati; Putri Audrey Zaskia Rohmadhona; Rosita Nugraheni (Universitas Negeri Surabaya, 2026)
This study aims to analyse the representation of intergenerational conflict in The Shadow’s Edge through a sociological approach by employing Karl Mannheim’s theory of generations as the primary theoretical framework. Intergenerational conflict is understood as a consequence of differences in socio historical experiences, value systems, and perspectives between older and younger generations. The study employs a qualitative method with content analysis as the main analytical technique. The primary data consist of the film The Shadow’s Edge, while secondary data are obtained through repeated observation of scenes that represent intergenerational conflict. The findings indicate that intergenerational conflict in the film is reflected through differences in working methods, professional ethics, and interpretations of technology between Wong Tak Chung as the representation of the older generation and He Qiuguo as the representation of the younger generation. The film further emphasizes that absolute reliance on technology has its limitations, while the empirical experience of the older generation remains relevant. Ultimately, The Shadow’s Edge portrays the reconciliation of intergenerational conflict through collaboration and the integration of perspectives, highlighting the importance of cross generational cooperation in addressing contemporary social challenges.